Políticas públicas socioambientais de gestão integrada para a conservação da biodiversidade no contexto urbano: proposta de Mosaico para as áreas protegidas da Pampulha, Belo Horizonte - MG - Gabriella Katlheen Leles (2023)
Urbanization is one of the main factors in habitat loss and fragmentation, in addition to causing several negative environmental and social effects. Intra-urban vegetation remains are an important ally in mitigating the impacts of urbanization, mitigating adverse environmental effects and improving people's physical and mental well-being. The Pampulha region, in the city of Belo Horizonte, is located in a transition zone between Cerrado and Atlantic Rain Forest, two biodiversity hotspots, further to its great historical and cultural importance. In this work, we justify the need to consolidate a Mosaico of urban protected areas in Pampulha, considering the important role that these areas play in the conservation of two threatened biomes and for the population of Belo Horizonte. We recorded the vertebrates richness in these protected areas in the SiBBR, GBIF and SpeciesLink Network databases, a document analysis through consultations with scientific publications and other documents, besides to observation data. Using a questionnaire adapted from the Rapid Assessment and Prioritization of Protected Area Management (RAPPAM), we carried out an environmental, socioeconomic, vulnerability and pressure diagnosis, and also management effectiveness of 15 protected areas in the Pampulha region, seeking to understand the strengths and weaknesses that require management attention. Furthermore, we constructed classification maps of vegetation cover and land use and characterized the vegetation cover, seeking to highlight the importance and benefits of conserving intra-urban vegetation fragments. We evidenced a great wealth of vertebrates for an urban area, with 367 species of vertebrates. The classification and characterization of the vegetation cover showed that the natural part (vegetation and water bodies) constitute 83.10% of the total cover, indicating a great potential for conservation of this ecotone region, even in small areas and with the presence of exotic species. The management assessment shows a medium effectiveness for the areas analyzed, with 52%, highlighting the need for public policies so that these areas are managed efficiently. There are still institutional and legal weaknesses for urban areas to be managed efficiently and therefore, through the mosaico management model proposed by the Sistema Nacional de Unidades de Conservação, we seek to support these areas legally, as well as emphasize the importance of urban fragments for conservation biodiversity and sociocultural aspects.